2021
DOI: 10.3389/fonc.2021.635329
|View full text |Cite
|
Sign up to set email alerts
|

Main N6-Methyladenosine Readers: YTH Family Proteins in Cancers

Abstract: Among the over 150 RNA modifications, N6-methyladenosine (m6A) is the most abundant internal modification in eukaryotic RNAs, not only in messenger RNAs, but also in microRNAs and long non-coding RNAs. It is a dynamic and reversible process in mammalian cells, which is installed by “writers,” consisting of METTL3, METTL14, WTAP, RBM15/15B, and KIAA1429 and removed by “erasers,” including FTO and ALKBH5. Moreover, m6A modification is recognized by “readers,” which play the key role in executing m6A functions. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 95 publications
(131 reference statements)
0
48
0
Order By: Relevance
“…YTH domain family proteins are collected by m6A and linked to several mRNA metabolism including mRNA splicing, translation, nuclear export, and mRNA degradation [ 13 , 14 ]. Therefore, YTH domain family proteins may be involved in many tumor physiological processes [ 8 , 15 ]. In literature, YTHDF1, an oncogene in HCC, is reported to promote the epithelial mesenchymal transition (EMT) of HCC cells by accelerating the translation of snail family transcriptional repressor 1 (SNAI1) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…YTH domain family proteins are collected by m6A and linked to several mRNA metabolism including mRNA splicing, translation, nuclear export, and mRNA degradation [ 13 , 14 ]. Therefore, YTH domain family proteins may be involved in many tumor physiological processes [ 8 , 15 ]. In literature, YTHDF1, an oncogene in HCC, is reported to promote the epithelial mesenchymal transition (EMT) of HCC cells by accelerating the translation of snail family transcriptional repressor 1 (SNAI1) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a recent study revealed that m6A is linked to the pathogenesis and development of HCC by regulating several targeted genes [ 7 ]. The YT521-B homology (YTH) domain family members, including YTHDC1, YTHDC2, YTHDF1, YTHDF2 and YTHDF3, are the main "m6A readers" [ 8 ]. Furthermore, YTH domain proteins are mostly enrolled in the tumorigenesis and tumor progression [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that these regulators were mutated in LUAD, although the alteration frequencies were not high (Figure 6A, less than 4%). M6A modifications of lncRNAs were also demonstrated as the powerful evidences in cancer researches (31,32). Studies also found that m6A regulators could trigger lncRNA expression.…”
Section: Identification Of Lncrna-tf Positive Feedback Loopsmentioning
confidence: 96%
“…However, selective depletion of ‘FTO’ not only increases sensitivity to anti-PD-1 therapy but also increases m6A methylation-inhibition of critical pro-tumorigenic (tumor-promoting) genes. Mechanistically, they proved that FTO-deficiency increases m6A-methylation at 5′UTR and 3′UTR of target genes; PD-1 (PDCD1), CXCR4 and SOX10, and thereby causing rapid mRNA-degradation by recruiting YTHDF2-reader proteins [ 155 , 157 , 158 ], confirmed by YTHDF2-knockdown in ‘increasing’ and YTHDF2-overexpression in ‘decreasing’ melanoma growth. Moreover, FTO-deficiency enhances the sensitivity of anti-PD-1 treatment by IFNγ-mediated cytokine response.…”
Section: Epitranscriptomics In Icb-therapeuticsmentioning
confidence: 99%
“…Epitranscriptomics generally referred to chemical modifications in the RNA molecule without changing the nucleotide sequence. So far more than 160 chemical modifications have been identified [ 151 ] playing a crucial role in regulating various biological processes, for example, in acute myeloid leukemia treatment [ 125 ], lung adenocarcinoma [ 152 ] gastric cancer [ 153 ] and broad range tumor types [ 151 , 154 , 155 ]. The major epitranscriptomic machineries (writer/editor, eraser/remover and readers/effector [ 156 ] not only regulate RNAs by specific regulatory mechanism [ 157 , 158 ] but also decide the fate of the cells and its associated immune disorders in cellular context-dependent manner.…”
Section: Epitranscriptomics In Icb-therapeuticsmentioning
confidence: 99%